(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
To reveal and compare the prevalence of pathotypes and virulence genes, as well as antimicrobial resistance and genotyping of poultry E. coli isolates from China and Algeria. Pathotype and seven virulence genes were tested by PCR, susceptibility to antimicrobials was evaluated using broth microdilution method, and genotyping was analyzed by PFGE. Six isolates were identified as pathogenic E. coli. Virulence gene testing showed that the frequency of ompT, iss, fimC, iroN, hlyF and iutA was high in the isolates from Shandong, Shanxi, Jiangsu and Xinjiang province, while stx2 was detected in only two isolates from Shandong, and stx2, iss, fimC, hlyF and iutA could not be detected in Tibet isolates. Importantly, nearly all isolates from Algeria carried seven virulence genes. Drug resistance testing of 141 strains showed that 98.2% (109/111) of the isolates from China and all isolates (30/30) from Algeria resist to more than three classes of antimicrobials. The PFGE genotyping of 157 isolates yielded 134 types, demonstrated a high level of genetic diversity among these isolates. Thus, the poultry E. coli from both China and Algeria exhibited either high frequencies of antimicrobial resistance or high rates of virulence genes carrying.